Odor Hedonic Profile (OHP): a self-rating tool of everyday odors - Charlotte, Bontempi; Laurence, Jacquot; Gérard, Brand (Frontiers in Neuroscience, 2023)
Odor hedonic estimation (pleasant/unpleasant) is considered the first and one of the most important dimensions in odor perception. Although there are several published scales that rate odor hedonicity, most of them use odorants that induce biases related to stimulus properties or test conditions and make difficult clinical or industrial applications. Thus, this study aimed to propose a model of odor hedonic profile (OHP) based on 14 items related to everyday odors without stimulus. The OHP is a self-rating tool based on the hedonic estimate representation and allows the determination of specific profiles, i.e., “conservative,” “neutral,” “liberal,” “negative olfactory alliesthesia,” and “positive olfactory alliesthesia.” It can be useful in different contexts (e.g., food studies) and general pathologies (e.g., eating disorders) or pathologies with mood/emotional disturbances (e.g., depression).